Keterbukaan Diri (Self Disclosure) Remaja yang Mengalami Disabilitas Fisik di Yayasan Pembinaan Anak Cacat (YPAC) Surakarta - Epti, Sandra Palestina; Hardew, Ayatullah Kutub (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Self-disclosure is an important aspect of adolescent social development, but for adolescents with physical disabilities, the dynamics influencing self-disclosure may differ from those of typically developing adolescents. The research question in this study is how the dynamics of self-disclosure manifest in adolescents with physical disabilities living in the YPAC Surakarta dormitory. The aim of this study is to understand the dynamics that influence self-disclosure in adolescents with physical disabilities at the Yayasan Pembinaan Anak Cacat (YPAC) Surakarta. The study employs a qualitative approach with a phenomenological framework, using semi-structured interviews as the data collection instrument. The study participants are adolescents aged 15 to 18 who have physical disabilities and have lived in the YPAC Surakarta dormitory for more than 6 months. The findings indicate that self-disclosure among adolescents with physical disabilities is influenced by several dynamics, including trust, emotional closeness, conversational context relevance, and personality. Trust is the primary dynamic that enables adolescents to share personal information, while emotional closeness and the relevance of the conversation context further facilitate self-disclosure. Introverted personalities tend to maintain privacy. In conclusion, self-disclosure among adolescents with physical disabilities is significantly influenced by the interaction between internal and external dynamics, and understanding these dynamics is crucial in creating a social environment that supports communication and their psychological well-being.